2017
DOI: 10.18553/jmcp.2017.23.8.893
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Formulary Restrictions on Patient and Payer Outcomes: A Systematic Literature Review

Abstract: This study was funded by Novartis Pharmaceuticals. Park and Ko are employed by Novartis Pharmaceuticals in East Hanover, New Jersey, and Ko holds stock in Novartis. Raza, George, and Agrawal are employed by Novartis Healthcare in Hyderabad, India. Study concept and design were contributed primarily by Park and Ko, along with the other authors. Raza, George, and Agrawal collected the data, along with Park and Ko. Data interpretation was performed by Agrawal, Raza, George, Park, and Ko. The manuscript was writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 45 publications
1
41
0
3
Order By: Relevance
“…[19][20][21][22] Although formulary restrictions are typically implemented to manage spending and drug utilization, 14 they can negatively impact medication fills and adherence. 23,24 Our results may provide context to the findings from a U.S. survey of transgender individuals, in which 25% of respondents reported being denied insurance coverage for hormone therapies. 3 These access barriers may result in higher OOP costs and lack of adherence to HT.…”
Section: Discussionsupporting
confidence: 56%
“…[19][20][21][22] Although formulary restrictions are typically implemented to manage spending and drug utilization, 14 they can negatively impact medication fills and adherence. 23,24 Our results may provide context to the findings from a U.S. survey of transgender individuals, in which 25% of respondents reported being denied insurance coverage for hormone therapies. 3 These access barriers may result in higher OOP costs and lack of adherence to HT.…”
Section: Discussionsupporting
confidence: 56%
“…Research addressing other aspects of health systems and insurers has shown that benefit design at this level, such as the use of prescription drug formularies, step therapy, and patient costsharing, can affect receipt of treatment and treatment adherence (49)(50)(51)(52)(53)(54). It is likely that health care system features, such as breadth and depth of provider networks, benefit design, routine use of EHR functionality in quality improvement, and financial assistance infrastructure, are associated with patient financial hardship, and these areas are important research gaps.…”
Section: Health Care System-level Risk Factors For Medical Financial mentioning
confidence: 99%
“…Because prior authorization has been shown to reduce access to medications, some public and private programs have removed prior authorization requirements for OUD medications. 15,16 However, prior authorization for buprenorphine is still common under Medicaid and private insurance. [17][18][19] Medicare Part D offers a unique opportunity to study the association of changes in prior authorization policies with the use of OUD medications and, more broadly, with health care Understanding how to improve OUD treatment access and outcomes among Medicare beneficiaries is important.…”
Section: Introductionmentioning
confidence: 99%